The Use of an Open-Ended Learning Approach on The Ability To Recognize The Concept of Numbers: Its Effectiveness for Children 4-5 Years Old - Warmansyah, Jhoni; Azizah, Faiha; Yuningsih, Restu; Sari, Meliana; Nurhasanah, Nurhasanah; Amalina, Amalina; Utami, Winda Trimelia (Universitas Nahdlatul Ulama Surabaya, 2023)
The formation of numerical concepts is a critical stage in early childhood development. Understandingnumbers lays the groundwork for future mathematical abilities and academic success. This study aimsto investigate the effect of an open-ended learning strategy on the capacity of 4-5-year-old childrento recognize number concepts. To reach the research goal, a quantitative approach was used, alongwith experimental methodologies. The study participants were children aged 4-5 years old, and datawas collected via total sampling. The experimental group was taught using an open-ended learningtechnique, while the control group followed a traditional structured teaching method. Pre-and post-testswere used to examine the children’s ability to recognize number concepts. Statistical analysis, includingt-tests, was used to compare the performance of the experimental and control groups. The results of thisstudy show that using an open-ended learning strategy improves the capacity of 4-5-year-old children torecognize number concepts. In comparison to traditional structured teaching method, the open-endedapproach stimulates active inquiry, independent thinking, and problem-solving, which improves children’scognitive development with regard to numerical concepts. This study suggests that open-ended learningtechniques are excellent educational strategies for developing number concept identification in youngchildren. This study’s findings have ramifications for early childhood educators and curriculum makers.This study stresses the necessity of implementing such tactics in educational settings by demonstratingthe benefits of an open-ended learning strategy in developing number concept awareness. Open-endedlearning techniques can improve children’s mathematics ability while also contributing to their generalcognitive development. Furthermore, these findings may motivate additional study and inquiry into theuse of open-ended learning approaches in various domains of early childhood education, increasing ourunderstanding of successful teaching strategies for young children.